2018
DOI: 10.1111/acfi.12342
|View full text |Cite
|
Sign up to set email alerts
|

Investor sentiment and the risk–return tradeoff in the Brazilian market

Abstract: This study examines the influence of investor sentiment on the risk–return relationship in the Brazilian stock market from 2002 to 2015. Using the Consumer Confidence Index as a substitute for the level of investor sentiment, we find that the relationship between conditional variance and stocks return is positive (negative) in periods of low (high) sentiment, except for small stocks, which always show a negative relationship between the constructs. The deterioration of the positive relationship between risk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
2
16
1
Order By: Relevance
“…Also, other irrational traders trade in concert in these high sentiment periods. This is consistent with the finding of a deterioration of the risk-return relationship in high sentiment periods due to the impact of less sophisticated noise traders (Antoniou et al, 2015;Kim, Kim, & Seo, 2017;Piccoli, Da Costa, Da Silva, & Cruz, 2018).…”
Section: Literature Reviewsupporting
confidence: 91%
“…Also, other irrational traders trade in concert in these high sentiment periods. This is consistent with the finding of a deterioration of the risk-return relationship in high sentiment periods due to the impact of less sophisticated noise traders (Antoniou et al, 2015;Kim, Kim, & Seo, 2017;Piccoli, Da Costa, Da Silva, & Cruz, 2018).…”
Section: Literature Reviewsupporting
confidence: 91%
“…Regarding companies' characteristics, Baker and Wurgler (2006) observed that companies that have characteristics associated with difficult pricing are evaluated in a non-homogenous way, allowing investor's sentiment to interfere with greater intensity in their pricing. In this sense, previous studies confirmed that, in some markets, the investor sentiment is more significant to explain the volatility of new companies in terms of listing, with a smaller size, higher growth pattern, and other characteristics that may cause uncertainties in their valuation compared to other companies (Baker & Wurgler, 2006, 2007Piccoli et al, 2018).…”
Section: Introductionmentioning
confidence: 74%
“…It can be impacted by quantitative and qualitative information, according to its value relevance (Galdi & Gonçalves, 2018). In view of the difficulty of traditional models in explaining market volatility, new factors are gaining importance, being investor sentiment one of these factors (Piccoli, Costa, Silva, & Cruz, 2018). After the 1980s, the literature started to consider that certain phenomena and market patterns, defined as anomalies, could be explained by peaks of investor irrationality driven by his/her sentiment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations